Diarrhea Control Strategies in the Islands: Interpretative Structural Modeling Analysis - Siti Chaerani Fatimah Apdin; Agus Bintara Birawida; Anwar Mallongi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Objectives: This research aims to determine the most dominant factors in the incidence of diarrhea, and design a diarrhea management strategy on Barrang Lompo Island. Methods: The research applies interpretative structural modeling (ISM) to map the relationships between key elements affecting of diarrhea control. The research instrument used was a questionnaire with a sample size of 7 informants including Government Institutions, Community Health Center Officers, Universities using the Interpretative Structural Modeling (ISM) Analysis method. Results: The research results showed that 7 elements analyzed, three were found to significantly impact diarrhea control : Food and drink sanitation, Personal hygiene (CTPS habits) and Availability of clean water. These insights can guide the development of health policies in island regions similar to the Barrang Lompo Islands. This study introduces a novel application of ISM to assess the factors affecting diarrhea management in an island context. Conclusion: The approach highlights the interconnected elements influencing diarrhea control in geographically isolated communities. The findings provide practical guidance for developing targeted health policies to improve both financial and health outcomes in similar regions. This research is valuable for policymakers, healthcare providers, and communities aiming to optimize resource allocation and improve hypertension management in remote areas.